Behaviour of lunar regolith simulants in fluidised bed reactors for in-situ resource utilisation. (January 2020) - Grill, L.; Ostermeier, P.; Würth, M.; Reiss, P.
Abstract: Gas-solid fluidised bed reactors play a major role in oxygen extraction from lunar regolith using a reduction gas. It is important to understand the flow hydrodynamics of the fluidised bed for reactor design, optimisation, and upscaling. The experimental study presented here investigates the fluidisation behaviour of the lunar regolith simulants EAC-1, JSC-1A, and TUBS-M in a gas-solid fluidised bed visually and through measurement of the pressure drop and heat transfer coefficient. The fluidisation behaviour of lunar regolith simulants is correlated with the solids properties. Furthermore, the relevance of detailed investigation of suitable regolith simulants for future lunar applications is discussed. Highlights: Regolith simulants can be fluidised under Earth gravity with nitrogen. Regolith simulants with similar properties differ in their fluidisation behaviour. Fluidisation behaviour is influenced by the particle size distribution. Lunar regolith has to be pre-processed (e.g. sieving) before fluidisation.